2021
DOI: 10.1111/ped.14606
|View full text |Cite
|
Sign up to set email alerts
|

Copy number alteration analysis for neuroblastoma using droplet digital polymerase chain reaction

Abstract: Background: Neuroblastoma (NB) is a malignant tumor derived from the neural crest. MYCN amplification is a well-known adverse molecular prognostic factor for NB. Genome copy number alterations (CNAs) such as chromosome (Chr) 11q deletion, 1p deletion, and 17q gain are associated with a poor prognosis. Fluorescence in situ hybridization (FISH) and Southern blotting analysis are frequently used to detect MYCN amplification. Although comparative genomic hybridization (CGH) and single-nucleotide polymorphism (SNP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Although this method is not currently used in clinical practice, it could be useful for detecting NB in broad screening protocols because of 17q gain's frequency [79]. Ishii et al developed a rapid droplet digital PCR method to detect 11q in NB samples, but they suggested the same technology could be reliably used for analyzing 17q [80]. FISH is frequently used in cytological laboratories to detect chromosome amplifications, deletions, and translocations.…”
Section: Alternative Methods For Identifying 17q Gainmentioning
confidence: 99%
“…Although this method is not currently used in clinical practice, it could be useful for detecting NB in broad screening protocols because of 17q gain's frequency [79]. Ishii et al developed a rapid droplet digital PCR method to detect 11q in NB samples, but they suggested the same technology could be reliably used for analyzing 17q [80]. FISH is frequently used in cytological laboratories to detect chromosome amplifications, deletions, and translocations.…”
Section: Alternative Methods For Identifying 17q Gainmentioning
confidence: 99%
“…Recently, droplet digital PCR (ddPCR) is being utilized as a robust method to detect copy number alterations with superior accuracy, also in MYCNamp detection of tumor tissues. [25][26][27][28] However, there are only limited reports regarding quantitative ddPCR analysis of MYCN copy number in plasma cfDNA. 12,17 In this study, we attempted a quantitative analysis of MYCNamp and 11qLOH, and also confirmed the utility of liquid biopsy in NB, by demonstrating presence of sufficient amount of tumor-derived cfDNA in plasma of NB patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, droplet digital PCR (ddPCR) is being utilized as a robust method to detect copy number alterations with superior accuracy, also in MYCNamp detection of tumor tissues 25–28 . However, there are only limited reports regarding quantitative ddPCR analysis of MYCN copy number in plasma cfDNA 12,17 .…”
Section: Introductionmentioning
confidence: 99%